Mao Tse-Tung On Guerrilla Warfare. - Griffith, General Samuel B. (Hauraki Publishing, 2015)
The Classic text on Communist Guerrilla warfare includes an excellent introduction by Brigadier General Samuel Griffith USMC who was also the translator. "In 1937 Mao ... wrote a succinct pamphlet that has become one of the most influential documents of our time ... the first systematic analysis of guerilla warfare ... The widespread applicability of Mao's doctrine stems from his realization of the fundamental disparity between the agrarian, peasant-based society of China and that of pre-revolutionary Russia, or any urban society ... he had to employ tactics and appeals appropriate to the peasant."